REPUTATION THREATS ANALYSIS IN THE BANKING SECTOR OF THE NORTH CAUCASIAN FEDERAL DISTRICT - Igor Kunitsyn (Вестник Северо-Кавказского федерального университета, 2022)
The author considered the emergence factors of commercial banks ' reputation risks, analysed the threats leading to loss of business reputation, estimated the reputation background of the banking sector of the North Caucasian Federal District, as well as the dynamics of credit institutions' ratings in the retrospective period.